Synthesis, Characterization and Antimicrobial Activities of Some Novel Derivatives of Phenol - Abdul Jameel, A.; Syed Ali Padusha, M. (Asian Journal of Chemistry, 2010)
Phenolic compounds and benzaldehyde have undergone condensation with compounds containing active hydrogen atom like urea, thiourea, semicarbazide and thiosemicarbazide. The compounds thus synthesized (I-XII) were characterized by elemental analysis, molecular weight determination by Rast micro method, TLC and melting point and spectral methods such as IR, 1H NMR, 13C NMR and mass. The antimicrobial activities of synthesized compounds were also studied.